An annotated pedigree of Neurospora crassa laboratory wild types, showing the probable origin of the nucleolus satellite and showing that certain stocks are not authentic. - D. Newmeyer; D. D. Perkins; E. G. Barry (Fungal Genetics Reports, 1987)
An annotated pedigree of Neurospora crassa laboratory wild types, showing the probable origin of the nucleolus satellite and showing that certain stocks are not authentic.